2021
DOI: 10.1186/s12967-021-02810-9
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplant procurement in the times of COVID-19: Quality report from the central European cryopreservation site

Abstract: Background Because of limitations of transportation imposed by the COVID-19 pandemic, current recommendation calls for cryopreservation of allogeneic stem cell transplants before patient conditioning. A single cell therapy laboratory was selected to function as the central cryopreservation hub for all European registry donor transplants intended for the Australian-Pacific region. We examined properties of these transplants to ascertain how quality is maintained. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
6
0
3
Order By: Relevance
“…9 Wiercinska and colleagues showed that median post-thaw recovery of viable CD34+ cells was 42% compared to viability > 90% prior to cryopreservation of HSC products. 15 Although in our center cell viability and CD34 + cell content is not routinely measured after thawing of cryopreserved grafts we were able to evaluate these parameters by flow cytometry in available samples from the cryopreserved grafts and compare them to prospectively freshly collected allogeneic graft samples. Importantly, we did not observe decrease in the absolute counts of CD34 + cells and HSC and only a slight decrease in viability, which was consistent among the cryopreserved samples.…”
Section: Discussionmentioning
confidence: 99%
“…9 Wiercinska and colleagues showed that median post-thaw recovery of viable CD34+ cells was 42% compared to viability > 90% prior to cryopreservation of HSC products. 15 Although in our center cell viability and CD34 + cell content is not routinely measured after thawing of cryopreserved grafts we were able to evaluate these parameters by flow cytometry in available samples from the cryopreserved grafts and compare them to prospectively freshly collected allogeneic graft samples. Importantly, we did not observe decrease in the absolute counts of CD34 + cells and HSC and only a slight decrease in viability, which was consistent among the cryopreserved samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation of hematopoietic progenitor cells (HPCs) in autologous and cord blood transplantation is a common practice. On the other hand, fresh allograft infusion is standard in allogeneic hematopoietic stem cell transplantation (allo-HSCT) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Fadeyi et al 15 observed that TNC viabilities were lower in cryopreserved/thawed grafts than in fresh (74% vs. 99%), engraftment times were similar when equivalent CD34 doses were infused. We did not request post‐thaw CD34 + cell recoveries since they are not routinely measured, but other studies indicate that they are highly variable with medians of 42%, 16 71%, 17 76% 18 and 87% 19 . Therefore, the dose of viable CD34 + cells received by patients is likely to be lower with cryopreserved grafts and may be at least partially responsible for the delays to engraftment.…”
Section: Discussionmentioning
confidence: 99%